2011
DOI: 10.1017/s1867299x0000074x
|View full text |Cite
|
Sign up to set email alerts
|

The Carmen Media Case – The Expected Catalyst from Brussels for a New Approach to German Gambling Law?

Abstract: Billions of Euros of turnover are generated every year from games of chance. The legal framework conditions regulating this branch of the economy vary significantly within the European Union. Whilst in many countries such as Germany the state has a dominating monopoly position, other Member States, such as Denmark, France and Italy, have made moves towards a consistent partial liberalisation. These different framework conditions lead to problems, increasingly so as the European internal market is otherwise gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…EU Member States have thus realised that it is better to have strict state control over organization of the games. (more on this in Spindler, Hambach, Berberich, 2011). In 2001 the German Federal Constitutional Court concluded that »the work of a casino on the whole is an unwelcome occupation that is nonetheless permitted by the government to check illegal gambling, to provide state-supervised opportunities for the human gaming instinct which cannot be restrained, and thereby to protect the natural passion for gambling from punishable exploitation« (ruling of 19 July 2001, cited in Meyer et al: 2009.…”
Section: Organisation Of Games Of Changean Unwelcome Occupationmentioning
confidence: 99%
“…EU Member States have thus realised that it is better to have strict state control over organization of the games. (more on this in Spindler, Hambach, Berberich, 2011). In 2001 the German Federal Constitutional Court concluded that »the work of a casino on the whole is an unwelcome occupation that is nonetheless permitted by the government to check illegal gambling, to provide state-supervised opportunities for the human gaming instinct which cannot be restrained, and thereby to protect the natural passion for gambling from punishable exploitation« (ruling of 19 July 2001, cited in Meyer et al: 2009.…”
Section: Organisation Of Games Of Changean Unwelcome Occupationmentioning
confidence: 99%